Relative expression and correlation of tumor necrosis factor-α, interferon-γ, and interleukin-17 in the rheumatoid synovium. Issue 7 (July 2016) - Nakajima, Arata; Aoki, Yasuchika; Sonobe, Masato; Watanabe, Fusako; Takahashi, Hiroshi; Saito, Masahiko; Nakagawa, Koichi
Abstract Although tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), and interleukin-17 (IL-17) play important roles in RA, their relative expression and possible correlation in synovial tissues are not well understood. In this study, mRNA expression levels of IFN-γ, IL-17, and TNF-α were investigated in individual patients with RA and the correlations between pairs of these three pro-inflammatory cytokines were analyzed. Synovial tissues were obtained during arthroplasties from 24 joints of 24 RA patients. After harvesting synovial tissues, total RNA was isolated then quantitative real-time polymerase chain reaction (qRT-PCR) for IFN-γ, IL-17, and TNF-α was performed. Correlation of expression levels between them was also analyzed. Expression levels of TNF-α, IFN-γ, and IL-17 in patients receiving TNF inhibitors (TNFi) and those treated with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) alone were also compared between groups. Based on relative expression levels of the three pro-inflammatory cytokines, patients were classified into three major types; an IFN-γ plus TNF-α-dominant type, an IL-17-dominant type, and the other type. TNF-α expression levels were correlated with IFN-γ. In addition, there was a negative correlation between TNF-α and IL-17, and IFN-γ and IL-17. Median relative expression levels of TNF-α have no significant difference between the TNFi and the csDMARDs groups. In the rheumatoid synovial tissues, expression levels of TNF-α were modulated in parallel with IFN-γ, and TNF-α and IL-17, or IFN-γ and IL-17 did not co-express at high levels. This characteristic expression pattern of the three pro-inflammatory cytokines may be clinically useful information in the current cytokine-targeted treatment with biological DMARDs for RA.